Study on Fatigue Life of Fractured Rock Under Constant Amplitude Cyclic Loading - Li, Run; Jian, Wenbin; Kang, Rongtao (Earth Sciences Research Journal, 2018)
The electro-hydraulic servo loading system was applied to make cyclic loading tests for fractured rock-like specimens. According to the results of the fatigue test, the power function model was used to fit and analyze the test data, and the fitting degree of the curve was determined by the correlation coefficient, and the result was fitted well. The main factors influencing the fatigue life of specimens were analyzed. The upper limit stress was the most important factor affecting the fatigue life of specimens. Under the same conditions, the specimen had a shorter fatigue life when being applied by higher upper limit stress; the rock of different types and strengths not only had different fatigue life, but also had the different sensitive degrees between the fatigue life and the upper limit stress; the fatigue life of specimens was significantly influenced due to different initial damages.